Critical education and the knowledge society: current challenges for the future of education in Nicaragua - Gudiel Gudiel, Denis Javier (Revista Multi-Ensayos, 2025)
In the educational field, multiple topics invite critical reflection, with the impact of the knowledge society being one of the most relevant. This argumentative essay addresses two fundamental questions within this context: Does current education allow for strengthening the bond between students and society? And what challenges does the knowledge society represent for the future of education in Nicaragua? To this end, several influential theoretical perspectives on education are analyzed and a position paper is constructed that articulates these visions with the challenges and opportunities posed by this society. It is recognized that both questions are broad and can be approached from various perspectives, which invites open reflection rather than definitive answers. Finally, a discussion of the educational reality in Nicaragua is offered, especially in relation to educational advances and limitations in addressing the questions posed.